(untitled) (Pathibhara Journal of Multidisciplinary Research, 2026)
Culture is the heart of human civilization and the distinct identity of any ethnic group. Festivals are the continuation of civilization because they preserve cultural heritage, transmit traditions across generations, and sustain social cohesion. The day culture and values disappear from a person’s life, that person can no longer be considered truly human. This research finds out the current status of Nachhiring cultures and festivals, which belong to the Kirat ethnic group in Nepal. It applies qualitative research methodology, using the ethnographic method. Participants include individuals from Sotang Rural Municipality, Solukhumbu district. Findings show that Nachhiring cultures and festivals are rapidly disappearing. Only the senior Nachhiring people are used to explaining the Nachhiring cultures and festivals and are worried about their innate extinction. Due to the modern education system, over-social network inclination, and governmental reluctance, minor ethnic treasures have been pushed to the margin. Realizing this harsh reality deeply, this research has been prepared with the objective of highlighting the importance and necessity of Nachhiring culture and festivals in the lives of today’s modern young students and youngsters.